Extracellular Vesicles Derived Human-miRNAs Modulate the Immune System in Type 1 Diabetes - Tesovnik, Tine; Kovač, Jernej; Pohar, Katka; Hudoklin, Samo; Dovč, Klemen; Bratina, Nataša; Trebušak Podkrajšek, Katarina; Debeljak, Maruša; Veranič, Peter; Bosi, Emanuele; Piemonti, Lorenzo; Ihan, Alojz; et al. (Frontiers in Cell and Developmental Biology, 2020)
Extracellular vesicles with their molecular cargo can modulate target cell response and may affect the pathogenesis of diseases. The extracellular vesicles containing micro-RNAs (miRNAs), which are often studied as disease biomarkers, but rarely as mediators of the disease development. The role of extracellular vesicles derived miRNAs in type 1 diabetes is currently not well established. We observed a fraction of blood plasma extracellular vesicles positive for membrane proteins potentially associated with insulin-producing beta-cells and identified differentially expressed extracellular vesicles derived miRNAs in individuals with type 1 diabetes. These differentially expressed extracellular vesicles derived human miRNAs in participants with type 1 diabetes and participants with Langerhans islets beta-cells destruction showed the ability to activate TLR7/8 signaling cascade and increase activation as well as cytotoxicity of the effector blood immune cells with cytokine and chemokine release. Our results illustrate extracellular vesicles derived human miRNAs as modulators of the immune system in type 1 diabetes autoimmunity, providing potentially new insight into the pathogenesis of the disease, and novel molecular targets for intervention and type 1 diabetes prevention.